Quercetin-conjugated magnetic nanoparticles inhibit Staphylococcus aureus growth and biofilm formation via downregulation of Coa and Hla genes - Alireza Habibi; Masoumeh Pakpour Roudsari; Seyyed Mahdi ZiaZiabari (AMB Express)
Abstract The research investigated the effects of that magnetic nanoparticles coated with the plant-based flavonoid quercetin have on the growth of Staphylococcus aureus. The synthesis of magnetic nanoparticles proceeded through co-precipitation and further involved quercetin coating using a dextran stabilizer. A combined product of these materials received the chemical name Fe3O4@Dex-QT. The study included multiple analytical tests such as FTIR (Fourier Transform Infrared Spectroscopy), FE-SEM (Field Emission Scanning Electron Microscopy), EDS (Energy-Dispersive X-Ray Spectroscopy) and XRD (X-ray diffraction) together with cellular and molecular assays. Biofilm detection experiments showed that 95% of studied microorganisms had moderate-to-strong biofilm formation abilities. The examined strains that formed biofilms exhibited complete biofilm inhibition at a minimum concentration of 512 μg/mL. Post-treatment with Fe3O4@Dex-QT nanoparticles, the Coa and Hla genes were expressed at 30 and 20% levels respectively, as determined through RT-PCR analysis. The research uncovered that Fe3O4@Dex-QT nanoparticles demonstrate successful antibacterial properties against S. aureus strains, making them viable for substituting conventional antibiotics. Graphical abstract